2013
DOI: 10.1002/cbin.10097
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia preconditioned human adipose derived mesenchymal stem cells enhance angiogenic potential via secretion of increased VEGF and bFGF

Abstract: Mesenchymal stem cells (MSCs) are adult multipotent cells found in bone marrow, adipose tissue, and other adult tissues. MSCs improve regeneration of injured tissues in vivo, but the mechanisms remain unclear. Typically, MSCs are cultured under ambient or normoxic conditions (21% O2 ). However, the physiological niches of MSCs have much lower oxygen tension. When used as a therapeutic tool to repair tissue injuries, MSCs cultured in standard conditions must adapt from 21% O2 in culture to <1% O2 in ischemic ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
106
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(115 citation statements)
references
References 23 publications
8
106
1
Order By: Relevance
“…Other investigators have demonstrated an increase in VEGF gene expression and secretion by MSCs in hypoxia. 14,15 Our results generally did demonstrate an increase in VEGF after hypoxia in 20% serum supplement, while the results are the opposite in 5% serum supplement. The serum levels may influence the gene expression for VEGF, so the secretion of VEGF in hypoxia was different between the 20% serum supplement and the 5% serum supplement.…”
mentioning
confidence: 48%
See 2 more Smart Citations
“…Other investigators have demonstrated an increase in VEGF gene expression and secretion by MSCs in hypoxia. 14,15 Our results generally did demonstrate an increase in VEGF after hypoxia in 20% serum supplement, while the results are the opposite in 5% serum supplement. The serum levels may influence the gene expression for VEGF, so the secretion of VEGF in hypoxia was different between the 20% serum supplement and the 5% serum supplement.…”
mentioning
confidence: 48%
“…[9][10][11] There is only 3%-14% oxygen in brain. 12 Hypoxia 13 can affect the secretion of paracrine factors, 14 alter gene expression of MSCs 15,16 and enhance proliferation of MSCs. [17][18][19][20][21] The amount of serum present in the culture media also affects stem cell behavior.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, when the angiogenic potential of MSCs was investigated in older subjects the resulting data demonstrated a reduced capacity for adipose-derived stem cells (ADSCs) to form capillary-like networks when compared with ADSCs isolated from younger subjects [40]. A MSCs capacity for vascularisation can be improved following hypoxic preconditioning [41]. This is significant given that low oxygen tension can result as a consequence of soft-tissue injury, and may implicate MSCs in ectopic bone formation (see Diagram 1).…”
Section: Mesoderm Mesenchymal Stem Cellsmentioning
confidence: 99%
“…In addition, VEGF has neurotrophic and neuroprotective effects in vitro and in vivo [23,24]. Although several studies have demonstrated that VEGF mRNA or protein expression is upregulated in hypoxia-preconditioned MSCs [25][26][27], few reports have demonstrated the neuroprotective effects of hypoxia-preconditioned MSCs transplantation to treat SCI. Therefore, the present study aimed to determine whether hypoxia-preconditioned MSCs have a neuroprotective effect in vitro and in vivo and improve functional defects in a rat model of SCI.…”
Section: Introductionmentioning
confidence: 99%